Immunoadjuvants for cancer immunotherapy - Carmona-Ribeiro, Ana Maria [UNESP] (Elsevier, 2024)
In cancer immunotherapy host immunity is recruited to kill cancer cells; approved clinical use of checkpoint inhibitors, for most patients, only partially removed the inhibition of T-cell functions against tumors, systemic T-cell responses have not been sufficient, low immunogenicity and the immunosuppressive environment of tumors have also been challenging for therapeutic efficiency in the clinic. Nanotechnology’s exponential growth has brought further developments for cancer immunotherapy. In this review, we mainly address how nanoengineered vaccines, combinatory therapies, oncolytic viruses and viral vectors, and nanostructures of diverse composition can induce robust T-cell responses against tumors and how nanomedicine can remodel the tumor immunosuppressive microenvironment to boost antitumor immune responses.
Keywords: Adjuvants for immunotherapy; cellular immunotherapy; chimeric antigen receptor-T cell; cytokines; immune checkpoint blockade; nanomaterials; nanovaccines; toll-like receptor agonists; tumor lysates as adjuvants